Gambaran Nilai Laju Endap Darah pada Perokok Elektrik (Vapor) di Kabupaten Tulungagung Jawa Timur - Wardani, Kartika Arum; Sundari, Vita; Chamidah, Nurul (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Erytdrocyte Sedimentation Rate in the speed of erythrocytes in precipitating non-cloting blood, with added anticoagulant which is placed in a westergreen tube vertically for 1 hour. Vapors in Tulungagung Regency began to develop rapidlu in the last 3 years. E-cigarettes are divided into several parts, including: the battery, the atomizer part that will heat and evaporate the nicotine solution, the cartidge containing the nicotine solution, the cartridgecontaining the nicotine solution. The risk of use does not only come from the batch brand of e-cigarettes, but also depends on the type of nicotine, the cleanliness of the e-cigarette and the factors of using e-cigarettes. Nicotine is an addictive substance in tobacco that can cause smokers to become dependent on cigarettes. The purpose of this study was to determine the value of the erythrocyte sedimentation rate in electric smokers (vapor) in Tulungagung Regency. Tube method used is a westergreen tube per hour with 30 samples of patiens using purposive sampling technique.The highest average yields were 15mm/hour. The highest average yields were 15mm/hour. This is due to vorious factors, including the length of use of e-cigarettes, age, liquid, smoking of e-cigarettes per day, and the per day, and the type of e-cigarette used. Keywords: Blood Sedimentation Rate, E-Cigarette, Risk Factor  ABSTRAK Laju Endap Darah ialah kecepatan eritrosit dalam mengendapkan darah (tidak menggumpal) dengan penambahan antikoagulan yang ditempatkan dalam tabung westergreen secara vertikal selama 1 jam. Perokok elektrik di Kabupaten Tulungagung mulai berkembang pesat dalam 3 tahun terakhir. Rokok elektrik terbagi menjadi beberapa bagian, antara lain: baterai, bagian atomizer yang akan memanaskan dan menguapkan larutan nikotin, cartridge berisi larutan nikotin, cartridge berisi larutan nikotin. Risiko penggunaan tidak hanya berasal dari merek batch rokok elektrik, tetapi juga bergantung pada jenis nikotin, kebersihan rokok elektrik, dan faktor penggunaan rokok elektrik. Nikotin merupakan zat adiktif dalam tembakau yang dapat menyebabkan perokok menjadi ketergantungan terhadap rokok. Tujuan dari penelitian ini adalah untuk mengetahui nilai laju sedimentasi eritrosit pada perokok elektrik di Kabupaten Tulungagung. Metode pemeriksaan yang digunakan adalah tabung westergreen per jam dengan sampel 30 pasien menggunakan teknik purposive sampling. Didapatkan hasil tertinggi adalah 15mm/jam. Pada penelitian disimpulkan hasil tertinggi adalah 15mm/jam, hal ini disebabkan oleh faktor rakus, antara lain lama penggunaan rokok elektrik, umur, cairan, rokok elektrik per hari, dan per hari, serta jenis rokok elektrik yang digunakan. Kata Kunci: Laju Endap Darah, Rokok Elektrik, Faktor Resiko